2019
DOI: 10.3390/cryst9070339
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Multi-Layer hBN on Ni(111) Substrates via MOCVD

Abstract: In this paper we demonstrate a metal organic chemical vapor deposition (MOCVD) process for growth of few layer hBN films on Ni(111) on sapphire substrates using triethylborane (TEB) and ammonia (NH3). Ni(111) was selected as a substrate due to its symmetry and close lattice matching to hBN. Using atomic force microscopy (AFM) we find hBN is well aligned to the Ni below with in plane alignment between the hBN zig zag edge and the <110> of Ni. We further investigate the growth process exploring interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Few-layer (∼6) hBN was grown on Ni by metal organic chemical vapor deposition at 900 °C. 54 hBN/SiO 2 /Si substrates for electronic measurements were prepared by wet transfer of hBN grown on Ni followed by Te sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…Few-layer (∼6) hBN was grown on Ni by metal organic chemical vapor deposition at 900 °C. 54 hBN/SiO 2 /Si substrates for electronic measurements were prepared by wet transfer of hBN grown on Ni followed by Te sputtering.…”
Section: Methodsmentioning
confidence: 99%
“…However, because of the non‐resonant character of Raman scattering in h‐BN, the signal in h‐BN is week less intense in contrast to graphene. This is due to the large h‐BN bandgap compared to available excitation energies in Raman spectroscopy . For pristine Sb 2 WO 6, Raman shifts are observed at around 130 cm −1 , 264 cm −1 , 422 cm −1 , 482 cm −1 , 714 cm −1 , 809 cm −1 and 869 cm −1 …”
Section: Resultsmentioning
confidence: 99%
“…[56,85] In contrast to TMDCs, few studies were reported on the growth of graphene and h-BN by the MOCVD process. [86][87][88] Examples of MOCVD processes used to grow TMDCs are illustrated in Figure 11b-f. The first paper in 2015 reported MOCVD growth of MoS 2 and WS 2 monolayer continuous films on 4 in.…”
Section: Mocvd Growth Processmentioning
confidence: 99%